2021
DOI: 10.1007/s11103-021-01152-w
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear GUCT domain-containing DEAD-box RNA helicases govern gametophytic and sporophytic development in Physcomitrium patens

Abstract: Key messageIn Physcomitrium patens, PpRH1/PpRH2 are GUCT-domain-containing DEAD-BOX RNA helicases localize to the nucleus. They are implicated in cell and tissue development in all stages of the moss life cycle. Abstract The DEAD-box-containing RNA helicase family encompasses a large and functionally important group of enzymes involved in cellular processes committed to the metabolism of RNA, including its transcription, processing, transport, translation and decay. Studies indicate this protein family has imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…From the 12 research articles, three studies concern the developmental biology field, including the regulation by miR171-GRAS module of plant meristem formation in P. patens (Beheshti et al 2021), the role of a subgroup of DEAD-box RNA helicases on both gametophytic and sporophytic development in P. patens (Perroud et al 2021), and a study on the conserved function of VASCULAR RELATED NAC-DOMAIN transcription factors during secondary wall formation in the peat moss Sphagnum palustre (Terada et al 2021). Further, Trogu et al reported the results of a multiplex gene editing technique for seven PHY genes using Multiplex CRISPR-Cas9 mutagenesis (Trogu et al 2020), and Furumizu and Sawa reported the molecular evolution of the subfamily X of Leucine-rich repeat receptor-like kinases using genomic information from a broad range of land plants, including hornworts, mosses and a liverwort (Furumizu and Sawa 2021).…”
mentioning
confidence: 99%
“…From the 12 research articles, three studies concern the developmental biology field, including the regulation by miR171-GRAS module of plant meristem formation in P. patens (Beheshti et al 2021), the role of a subgroup of DEAD-box RNA helicases on both gametophytic and sporophytic development in P. patens (Perroud et al 2021), and a study on the conserved function of VASCULAR RELATED NAC-DOMAIN transcription factors during secondary wall formation in the peat moss Sphagnum palustre (Terada et al 2021). Further, Trogu et al reported the results of a multiplex gene editing technique for seven PHY genes using Multiplex CRISPR-Cas9 mutagenesis (Trogu et al 2020), and Furumizu and Sawa reported the molecular evolution of the subfamily X of Leucine-rich repeat receptor-like kinases using genomic information from a broad range of land plants, including hornworts, mosses and a liverwort (Furumizu and Sawa 2021).…”
mentioning
confidence: 99%